Research on innovative design of Nuo mask based on Memetics-AHP-Thematic analysis-shape grammar - Axiang Yang; Leqiong Wang; Wangqun Xiao; Long Chen; Xinye Liao (PLoS ONE, 2025)
The study seeks to investigate the cultural factors of Chizhou Nuo masks and their strategic application strategies in contemporary design, by compiling the Chizhou Nuo cultural literature, integrating memetics, identifying the cultural factors of the Chizhou Nuo masks, and then developing the genetic mapping of the Chizhou Nuo mask culture. Simultaneously, the analytic hierarchy process (AHP) is employed to objectively allocate weights to design considerations, ascertain the significance of each cultural factor, and prioritize their value, thereby filtering the necessary design elements. Subsequently, thematic analysis to employed to examine the interview data, yielding an indicator of consumer demand. The shape grammar was ultimately utilized to produce a design product that adheres to modern aesthetic criteria. The fuzzy comprehensive evaluation (FCE) method is used to evaluate the design scheme, select the optimal design scheme, and guide further design optimization. This study investigates a novel paradigm for the design and evaluation of Chizhou Nuo mask cultural and creative items utilizing memetics, AHP, thematic analysis, shape grammar, and FCE. The model’s practicality is validated through the design cases of Chizhou Nuo mask graphic design. It offers novel theoretical and practical direction for the designers of future intangible cultural and creative products. Furthermore, it offers a novel avenue for the preservation and advancement of intangible cultural heritage.